Report of Steering Committee Perspective Planning for Transport Development - Planning Commission (Planning Commission, 1988)
The Committee, after a review of the past experience of transport planning in India and some other countries, came to the conclusion that in the current state of data availability, it was not practical to develop an all-purpose model for investment planning for the sector. As such, the Committee has adopted alternative approaches based on development of a series of models to project transport demands for certain bulk commodities and determination of capacity needs, on high density routes/corridors
Planning Commission Government of India
Planning Commission Government of India